Legal Analysis of The Proof Strength of Visum Et Repertum in Cases of Assault Resulting in Death (Decision Number 1294/2025Pid.B/PN Mdn) - Ariel Pasudeo Hutabarat; July Esther; Jusnizar Sinaga (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2026)
Criminal evidence is crucial for justice, where Visum Et Repertum as expert testimony (Article 184 paragraph 1 of the Criminal Procedure Code) proves the causal relationship between the assault and the victim's death. This case involves defendants Revan Rainsyah and Hanif who committed assault together against Fajar Marlaba Khudri on May 2, 2025 in Medan, using sharp weapons until the victim died. The research is normative, prescriptive, and analytical juridical, examining positive legal norms, court decisions, and theories such as negative wettelijk bewijsstelsel and presumption of innocence. The approach includes a statute approach (Criminal Procedure Code Articles 184-188), a case approach (analysis of decisions), and a conceptual approach (doctrine of evidence). Visum Et Repertum Number 45 / VER / V / 2025 / RS Bhayangkara (dr. Surjit Singh, Sp.FK) proves head lacerations, skull fractures, and brain hemorrhages on the victim's body, strengthening witness testimony, clues, and forming the judge's conviction. The judge fulfilled the elements of Article 354 paragraph 2 in conjunction with Article 55 paragraph 1 of the Criminal Code, imposing a sentence of 7 years and 6 months in prison for each defendant, taking into account aggravating factors (victim's death, public unrest) and mitigating factors (regret, zero recidivism).